A review of touch research in consumer psychology - Krishna, Aradhna; Luangrath, Andrea Webb; Peck, Joann (Journal of Consumer Psychology, 2024)
AbstractThis article details the theoretical foundation of haptics in consumer research. We structure the review using a continuum from proximal touch‐based interactions to increasingly distal interactions through devices, imagery, or language use. We begin with a focus on product/object touch in marketing highlighting touch for haptic information, touch for haptic pleasure, and touch for nonhaptic functional reasons. We then elaborate on research considering work compensating for actual touch through various mechanisms including device‐mediated touch and imagery processing. Next, we examine interpersonal touch followed by a discussion on touch in sensory words and textual paralanguage. The authors note various avenues for future research in haptics with the aim to encourage research in consumer psychology and marketing.